Humanitarian civil engineering : practical solutions for an interdisciplinary approach - Kremmyda, Georgia, 1979- (ICE Publishing, 2021)
Enabling the safety of life and property against humanitarian challenges is the highest call of the civil engineering profession. However, it cannot be done by civil engineers alone. What can civil engineers learn from other professions and interdisciplinary approaches and how can that inform them in making an effective difference to the world. 'Humananitarian Civil Engineering' makes the case for the pivotal role of civil engineering in takling global humanitarian challenges. It aims to identify what a humanitarian engineer does, offers practices that are tangible to ensure safe engineering and combines concepts and tools traditionally used by practitioners and development agencies with civil engineering practices, project management and systems thinking.